A disability aware approach to torture prevention? Australian OPCAT ratification and improved protections for people with disability. Issue 1 (2nd January 2018) - Lea, Meredith; Beaupert, Fleur; Bevan, Ngila; Celermajer, Danielle; Gooding, Piers; Minty, Rebecca; Phillips, Emma; Spivakovsky, Claire; Steele, Linda; Wadiwel, Dinesh Joseph; Weller, Penelope June
ABSTRACT: In 2017, Australia ratified the Optional Protocol to the Convention against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment (OPCAT). Ratification of OPCAT presents as a unique opportunity to highlight the institutional treatment of people with disability in a range of sites of detention within Australia and build on advancing international protections for people with disability, including those articulated in the Convention on the Rights of Persons with Disabilities (CRPD). This article considers the opportunity presented by OPCAT for improving protections for people with disability against torture and ill-treatment. The article argues for an expansive definition of 'sites of detention' that is able to encapsulate both disability-specific and mainstream settings in which people with disability may be deprived of their liberty, as well as to address specific practices such as the use of mechanical restraint, chemical restraint and seclusion. Based on an analysis of international National Preventive Mechanism (NPM) models, it is further argued that people with disability, their representative bodies and other civil society actors must be meaningfully involved in NPM processes, including in the monitoring of sites of detention, and the identification of systemic issues affecting people with disability with lived experience of detention.